Pengembangan Media Interaktif Powerpoint Profil Pelajar Pancasila untuk Siswa Sekolah Dasar - Ranti Ranti; Eddy Noviana; Munjiatun Munjiatun; Guslinda Guslinda (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study evaluates the feasibility of the interactive PowerPoint media *Profil Pelajar Pancasila* for 5th-grade elementary school students. Using the Borg & Gall Research and Development (R&D) model, data were collected through surveys, interviews, questionnaires, and validation sheets, analyzed both quantitatively and qualitatively. Media expert validation scored 92, averaging 4.84 (96.84%, "Highly Feasible"). Material expert validation scored 49, averaging 4.08 (81.67%, "Highly Feasible"). Student feedback showed 68% (17 students) rated the media as "Highly Feasible" with scores above 80%, while 32% (8 students) rated it "Feasible," with scores from 61.33% to 78.67%. The overall score was 1609, with an average percentage of 85.71%, categorized as "Highly Feasible." Teachers gave similarly positive evaluations. Teacher 1 scored 81 (95.29%), and Teacher 2 scored 69 (81.18%), both rated as "Highly Feasible." In conclusion, the interactive PowerPoint media *Profil Pelajar Pancasila* is deemed "Highly Feasible" by media and material experts, students, and teachers, proving its effectiveness and suitability for elementary education.Keywords: PowerPoint, Interactive Media, Pancasila Student Profile.